Self-concept, Hope and Achievement: A look at the relationship between the individual self-concept, level of hope, and academic achievement - Yahaya, Azizi (2006)
Abstract: A review of the available literature reveals a link between factors of an individual self-concept, their level of hope and achievement. Hope can be the impact on an individual confidence in his or her ability to perform a behavior that will lead to a goal. Differences between students and teachers’ perception were evidence of the teachers unwillingness to admit that they have negative feeling towards low achieving students. Students and their teachers agreed that low-achieving students get more teachers help and support and less pressure. With regard to praise and criticism, however, teachers and student held opposing view. Hence, students’ perception of their treatment were found to be related to teacher expectancy as well as to students’ school self-concept. The study also aimed to identify achieving students who did nit receive special consideration. The particular aspects of self-concept investigated were global self-concept, and the related domain specific areas of social, family/home and scholastic self-concept. Teacher ratings of pupil self-concept were also obtained to identify whether there were significant discrepancies between how children perceived themselves and how they were perceived by teachers